Stochastic behaviour of the Athens stock exchange - Theodossiou, Panayiotis; Koutmos, Gregory; Negakis, Christos (My University, 1993)
The stochastic behaviour of stock prices on the Athens Stock Exchange in Greece is investigated. The methodology employed is Nelson's (1991) exponential GARCH-M model, which allows shocks to have an asymmetric impact on volatility. The findings suggest that both the first and the second moments of the distribution of returns are time-dependent, and as such cannot be modelled as white-noise processes. Specifically, volatility is an asymmetric function of past shocks in the sense that positive shocks have a greater impact on volatility than negative shocks. When returns are measured in dollar terms, the estimated risk premium is positive and significant, i.e. returns are positively related to volatility. These findings are in contrast to those discovered by other studies for the US stock prices, e.g. Pagan and Schwert (1990) and Nelson (1991).